Four : a Divergent collection - Roth, Veronica (Divergent, 2014)
"A collection of four pre-Divergent stories plus three additional scenes from Divergent, all told from Tobias's point of view, that follow Tobias's transfer from Abnegation to Dauntless, his Dauntless initiation, the first clues that a foul plan is brewing in the leadership of two factions, and the weeks after he meets Tris Prior"--Provided by OCLC.